2012
DOI: 10.22605/rrh1900
|View full text |Cite
|
Sign up to set email alerts
|

The influence of motivation in recruitment and retention of rural and remote allied health professionals: a literature review

Abstract: The influence of motivation in recruitment and retention of rural and remote allied health professionals: a literature review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 47 publications
(67 reference statements)
6
69
0
Order By: Relevance
“…These findings are in keeping with several studies which have highlighted family and lifestyle as key motivating factors for retention in rural practice (Gallego et al, 2015;Keane et al, 2012). A review of incentives for rural health workforce retention by Campbell et al (2012) found that a rural lifestyle and having family nearby were key incentives for remaining in rural practice. Furthermore, Keane et al (2011) found that work/life balance was the most common reason given for rural allied health practitioners choosing their current role.…”
Section: Ideal Practice Location For Graduates From a Rural Speech An...supporting
confidence: 88%
See 2 more Smart Citations
“…These findings are in keeping with several studies which have highlighted family and lifestyle as key motivating factors for retention in rural practice (Gallego et al, 2015;Keane et al, 2012). A review of incentives for rural health workforce retention by Campbell et al (2012) found that a rural lifestyle and having family nearby were key incentives for remaining in rural practice. Furthermore, Keane et al (2011) found that work/life balance was the most common reason given for rural allied health practitioners choosing their current role.…”
Section: Ideal Practice Location For Graduates From a Rural Speech An...supporting
confidence: 88%
“…The link between increased age and retention in the rural workforce has been established in numerous studies (Daniels et al, 2007;Humphreys et al, 2010;Keane et al, 2011;Stagnitti et al, 2005) and the current findings are in support of this suggestion. It has been suggested that this may be due to younger professionals seeking further career opportunities and professional development that may not be available in rural areas (Campbell et al, 2012).…”
Section: Ideal Practice Location For Graduates From a Rural Speech An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in Australia has shown that sourcing future workers from a rural background, coined the 'rural background effect' (11), is a strong predictor of future entry into rural practice (12). Additionally, a desire for a rural lifestyle, being connected to the community, an enjoyable patient base, and the autonomy offered by the nature of rural work are factors shown to positively influence rural health workforce recruitment and retention (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…When red flags (e.g., cancer, fracture) are absent, the most appropriate management of musculoskeletal conditions is the conservative interventions which are tailored according to the patient's clinical presentation and needs [3]. Limited provision of medical services to patients in remote and rural areas had been associated with poor recruitment and retention of clinicians [4]. Geographic reasons and shortage of staff are not the only reasons for limited service provision.…”
Section: Introductionmentioning
confidence: 99%